Lecturers’ Narrative Writing Teachability as Proven in Students’ Short Story Performance - Sumekto, Didik Rinan; Putri, Novita Sumarlin; Munifah, Ike Zakiah (Bina Nusantara University, 2023)
The research aimed to observe the lecturer’s teachability on students’ short story performance based on the database fitness of narrative writing. The research involved 245 undergraduate students aged between 18 to 23 years old (Mage = 20,65; SD = 1,603), from the parallel-intact-narrative writing. Students’ self-rated evaluation used several variables: transparency, accountability, fairness, and assistance in narrative writing instruction. Meanwhile, short story samples verified vocabulary, structure, mechanics, content, and organization. The findings show the lecturer’s teachability in the moderate category, for which the independent T-test results do not statistically show a significant difference between male and female students for perceiving the lecturer’s teachability, and the MANOVA revealed the lecturer’s teachability with F (16, 724.687), p = 0,044; Wilks’ Lambda = 0,894; and partial eta squared = 0,028, determined a differently statistical significance. The Systematic Analysis of Language Transcripts (SALT) indicates students’ short story samples with some experience of the syntactic structures and various categories upon the correlational results since the transcript length intelligibility, standard measures, and subordination index signified the database for supporting students’ short story performance.